ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN MEETING ROOM DI GOLDEN FLOWER HOTEL BANDUNG - GIAN DWI AFRIANDI, - (2016)
Penelitian ini membahas tentang faktor apa saja yang paling dominan yang mempengaruhi keputusan penggunaan meeting room di Golden Flower Hotel Bandung dan upaya yang apa saja harus dilakukan oleh pihak pengelola Golden Flower Hotel Bandung untuk meningkatkan jumlah penggunaan meeting room. Tujuan dari penelitian ini adalah untuk mengidentifikasi faktor apa saja yang paling dominan yang mempengaruhi keputusan penggunaan meeting room di Golden Flower Hotel Bandung dan juga untuk menganalisis upaya yang harus dilakukan guna meningkatkan penggunaan meeting room. Metode yang digunakan dalam penelitian ini adalah metode deskriptif-kuantitatif, dengan menggunakan teknik analisis data analisis faktor confirmatory. Dari 12 butir indikator yang penulis sebar dengan menggunakan kuesioner yang dibagikan kepada 50 pengguna meeting room, didapatkan temuan bahwa terdapat 4 faktor bentukan baru yang paling dominan dalam mempengaruhi keputusan penggunaan meeting room di Golden Flower Hotel Bandung. ke empat faktor tersebut antara lain faktor quality, repeater, and external dealer; faktor image, payment services, and sales/marketing; faktor quality and function, and amount purchase; dan faktor easy payment method and reserve purchase. Dari ke empat faktor tersebut terdapat dua faktor yang paling mempengaruhi yaitu faktor quality, repeater, and external dealer dan faktor image, payment services, and sales/marketing. Adapun upaya yang harus dilakukan oleh pihak Golden Flower Hotel Bandung guna meningkatkan jumlah penggunaan meeting room yang mengacu kepada temuan yang didapat antara lain, mempertahankan kualitas meeting room dan meningkatkan kerja sama dengan pihak travel agent, Event Organizer, Profesional Organizer, dan Training Provider.;---This research discussed about the factors that most the dominant influence the meeting room user desicion at Golden Flower Hotel Bandung and efforts to what needs to be done by the management of the Golden Flower Hotel Bandung to increase the number of the use of meeting rooms. The purpose of this research is to identify factors are the most dominant desicion that influenced the use of meeting room at the Golden Flower Hotel Bandung and also to analyze the efforts to do in order to increase the use of meeting rooms. The method used in this research is the method of descriptive - quantitative, by using a technique confirmatory - factor analysis. 12 indicators of the author of the spread of using questionnaires that distributed to 50 meeting room users, its got the findings that there are four new factors by most dominant in affected the desicion of the meeting room user. The four of these factors, among other, quality, repeater, and external dealer factor; image, payment services, and sales/marketing factor; quality and function, and amount purchase factor; and easy payment method and reserve purchase factor. Of those four of these factors there are two factors that most most affect, that is quality, repeater, and external dealer factor; image, payment services, and sales/marketing factor. The efforts that need to be done by Golden Flower Hotel Management in order to increase the number of the use of meeting rooms are referring to the findings obtained, that is, maintaining the quality of the meeting room and improve coorperation with the travel agent, Event Organizer, Profesional Organizer, and Training Provider.